Helicobacter pylori의 위상피세포 유착에 관한 전자현미경적 고찰 - 현진해; Jin Hai Hyun; 엄창섭; Chang - Sub Uhm; 김창덕; Chang Duck Kim; 류호상; Ho Sang Ryu; 이성일; Sung Il Lee; 전훈재; Hoon Jai Chun; et al. (The Korean journal of medicine, 2001)
Background : The purpose of this study was to investigate the ultrastructural relation of H. pylori and gastric epithelial cells in their adhesion. Methods : Endoscopic biopsy of gastric antrum and body was performed from 15 patients (9 men, 6 women) with chronic gastritis. These specimens were processed and observed by transmission electron microscope (Hitachi H-600). Results : On the basis of morphological appearances, the different types of adhesion of the organism with the epithelial cells were categorized as filamentous connection, adhesion pedestals, membrane fusion. Coccoid and intermediate forms were associated with filamentous connection whereas bacillary forms were associated with adhesion pedestals and membrane fusion. Conclusion : Various types of adhesion were associated with H. pylori and gastric epithelium. Further studies are needed to investigate biophysiologic influence to epithelial cells by ultrastructural relationship.(Korean J Med 60:16-21, 2001)